PENDAMPINGAN MEMBACA AL-QUR'AN DALAM MENINGKATKAN KEFASIHAN MENGGUNAKAN METODE TILAWATI DI TPA SIRAJUL JAMA’AH - Aprilia Rizqi Permatasari; Anita Rahmayani (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study aims to describe the process and results of mentoring reading the Qur'an in improving the fluency of students using the Tilawati method at the Sirajul Jama'ah Al-Qur'an Education Park (TPA). The background of this study is based on the importance of the ability to read the Qur'an fluently as part of basic Islamic education. The Tilawati method was chosen because it has a systematic approach and is oriented towards training in makharijul huruf, tajwid, and reading fluency. This study uses the Servic Learning method. Data collection techniques are carried out through observation and documentation. The results of the study indicate that routine and intensive mentoring with the Tilawati method can improve the fluency of reading the Qur'an of children, both in terms of pronunciation of hijaiyah letters, mastery of tajwid laws, and reading fluency. Supporting factors for the success of mentoring include teacher commitment, parental involvement, and a conducive learning environment. This study recommends the consistent application of the Tilawati method as one of the effective strategies in improving the ability to read the Qur'an in non-formal educational institutions.